2021
DOI: 10.5334/joc.140
|View full text |Cite
|
Sign up to set email alerts
|

Do All Switches Cost the Same? Reliability of Language Switching and Mixing Costs

Abstract: The current study examined the reliability and consistency of switching and mixing costs in the language and the color-shape tasks in three pre-existing data sets, to assess whether they are equally well suited for the study of individual differences. Specifically, we considered if the language task is as reliable as the color-shape task-an important question given the wide use of language switching tasks but little information available to address this question. Switching costs had low to moderate reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Many of these studies relied on the absence of significant correlations between different tasks purporting to measure the same construct. However, such correlations are only informative when there are robust and stable individual differences, which these tasks were not designed to measure (Draheim et al, 2020; Hedge et al, 2018; Segal et al, 2021); and the interpretation of null effects is necessarily limited, requiring high power to observe the effects, inclusion of well-matched groups, and exclusion of older participants with mild cognitive impairment. Recent meta-analytic evidence suggests that the most robust aging-related declines in executive control include the ability to inhibit a prepotent response as measured by stop-signal or go-no-go tasks (Rey-Mermet & Gade, 2018; Rey-Mermet et al, 2018), which speculatively, could be analogous to a failure to reverse language dominance in the aging group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies relied on the absence of significant correlations between different tasks purporting to measure the same construct. However, such correlations are only informative when there are robust and stable individual differences, which these tasks were not designed to measure (Draheim et al, 2020; Hedge et al, 2018; Segal et al, 2021); and the interpretation of null effects is necessarily limited, requiring high power to observe the effects, inclusion of well-matched groups, and exclusion of older participants with mild cognitive impairment. Recent meta-analytic evidence suggests that the most robust aging-related declines in executive control include the ability to inhibit a prepotent response as measured by stop-signal or go-no-go tasks (Rey-Mermet & Gade, 2018; Rey-Mermet et al, 2018), which speculatively, could be analogous to a failure to reverse language dominance in the aging group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are two alternative explanations for the absence of significant correlations between the switch costs. Firstly, concerns have been raised about the reliability of difference scores and this could explain the discrepancy in findings between the switch costs (a difference score) and overall RTs (e.g., Draheim et al, 2019;Segal et al, 2021). Secondly, methodological differences may hinder the comparison between types of switching (Declerck et al, 2017(Declerck et al, , 2020.…”
Section: Contributors To Language Switching Abilitiesmentioning
confidence: 99%
“…While true multi-linguals may not demonstrate any difficulties in switching languages, the "non-native" speaker may perceive it as quite challenging to prevent intrusions of their mother tongue when speaking the secondary language. Segal et al (2021) suggested bilingual language use might rely on processes involved in non-linguistic multitasking. In order to develop a procedure for testing their hypothesis, the authors studied the reliability and consistency of both switching and mixing costs in the context of bilingualism asking whether language-based tasks would be subject to similar individual differences as observed in non-linguistic colour-shape tasks.…”
mentioning
confidence: 99%